Inovasi LKPD digital berbantuan canva berbasis problem based learning dalam meningkatkan kemampuan pemecahan masalah matematis siswa SMP - Adisya Hilwa Aufazzahra; Wahyu Hidayat; Siti Chotimah (JPMI (Jurnal Pembelajaran Matematika Inovatif), 2026)
This study focuses on the development of digital flipbook-formatted LKPD, using a Problem-Based Learning approach for the topic of algebraic forms. The method used is Research and Development by following the ADDIE model. The subjects in this study were 31 seventh-grade students. Data collection was carried out using validation sheets, student response questionnaires, and tests. From the research findings, it was obtained that the LKPD had an average validity score of 4.61 (very valid), while the validity of the material content reached 90.48%. The level of practicality, reached 76.13% (practical). The N-Gain analysis produced a value of 0.7526, which confirms an increase in students' mathematical problem-solving abilities in the high category. Given that the data were not normally distributed, further analysis was performed using the Wilcoxon test, which showed a significance value of 0.000 (<0.05). This indicates a significant difference between the pretest and posttest results. The successfully developed student worksheet LKPD is expected to be a valid, practical, and effective digital teaching material option. Consequently, this LKPD has the potential to be an innovative learning medium capable of optimizing students' mathematical problem-solving abilities at the junior high school level.